Control motion: Notions - Yáñez-Valdez, Ricardo (My University, 2018)
Motion Control is a sub-field of automation encompassing the systems or sub-systems involved in the moving parts of machines in a controlled manner. Using a computer to control an actuator offers benefits, but today getting data and feedback is increasingly important. Motion control may be open loop or closed loop. In open loop systems, the controller sends a command through the amplifier to the prime mover or actuator, and does not know if the desired motion was actually achieved. Typical systems include stepper motor. For tighter control with more precision, a measuring device may be added to the system (usually near the end motion). When the measurement is converted to a signal that is sent back to the controller, and the controller compensates for any error, it becomes a Closed loop System.
This is a brief resume about control motion. Essential knowledge for the movement of machines in the design stage.
Keywords: Accuracy; ball screws; microstepping; repeatability; resolution